Influence of Anastrepha fraterculus (Diptera: Tephritidae) larval instars on the production of Diachasmimorpha longicaudata (Hymneoptera: Braconidae) progeny and their sex ratio - Van Nieuwenhove, Guido Alejandro (2011)
The aim of this study was to determine the optimal larval age for exposing Anastrepha fraterculus (Wiedemann) to Diachasmimorpha longicaudata (Ashmead) females to maxi- mize parasitoid female offspring production under laboratory conditions in order to develop an efficient mass-rearing process for this biocontrol agent. Five age ranges of A. fraterculus larvae were assessed: 1-3 d-old (first instar), 4-6 d-old (second instar), 7-8 d-old (early third instar), 9-10 d-old (middle third instar), and 11-12 d-old (late third instar). The number of D. longicaudata initiating ovipositor probing on a device with third instars of A. fraterculus was significantly higher than with others containing younger instars. Although female biased parasitoid offspring was recorded in all treatments using third instars as hosts, significantly more D. longicaudata females emerged from A. fraterculus pupae originated from middle and late third instars. However, the percentage of unemerged host puparia also increased significantly in both those host instar groups. Superparasitism, recorded as the number of first instar parasitoid head capsules per host, increased significantly as A. fraterculus larvae matured from second instars to late third instars. Nevertheless, the maximum average yield of parasitoid progeny was achieved using 9-12 d-old A. fraterculus larvae as hosts.